The prospects and user perceptions of m-banking in the Sultanate of Oman - Sadi, A.H.M. Saifullah; Azad, Imran; Noordin, Mohamad Fauzan (2010)
Mobile commerce known as M-commerce is an emerging discipline that involves mobile device, wireless networks and Internet technologies. M-Commerce refers to the different types of business transactions that are conducted on mobile devices using wireless networks. Mobile banking or M-banking is also equally refereed as mobile E-banking. It is considered to be the latest gateway in electronic banking that provides a platform for doing banking transactions using mobile telecommunication devices. The aim of this paper is to investigate the level of adoption of Information and Communications Technology (ICT) in the banking sector and to assess the prospects of M-banking in Oman. The findings shows that most of the banks and the telecoms operators have the strengths to offer better qualities of electronic and mobile services to the residents of Oman. Currently, the banks are trying to offer one form of M-Banking or the other, but the weaknesses are the level of patronage and fewer services. The level of patronage is low and it requires concerted efforts of the telecoms operators and the financial institutions to fast-track the development of M-Banking services to the people. It is expected that recent development of 3G (Third Generation) network will boost M-Commerce activities in the sultanate of Oman but may require further investment in the quality of cell phones and mobile network.